Pengaruh Content Marketing Dan Online Customer Review Terhadap Minat Beli Konsumen Pada Produk Indomilk Durian Musang King di Tik Tok Shop (Studi Pada Konsumen Kecamatan Babelan) - Firdaus, Ahmad Ferdi; Sukirno, Sukirno (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Online shopping platforms have reshaped consumer behavior, prompting companies to adopt interactive and experience-based promotional strategies. This study aimed to analyze the influence of content marketing and online customer reviews on consumer purchase intentions for Indomilk Durian Musang King products on TikTok Shop, focusing on consumers in Babelan District. Using a quantitative survey method, data were collected from 110 respondents who had purchased Indomilk and seen advertisements for the Durian Musang King variant. Multiple linear regression was used for data analysis. The findings revealed that content marketing (X1) had a positive and significant partial effect on purchase intention by 50.3%, while online customer reviews (X2) had a stronger positive effect of 66.8%. Simultaneously, both variables influenced purchase intention (Y) by 67.8%, with the remaining 32.2% attributed to other factors not studied, such as price, product quality, and brand image. These results highlight the strong role of digital engagement in driving consumer decisions.